Analisis Faktor Aktivitas Ekonomi Kaum Perempuan Nagari Guguak VIII Koto Kecamatan Guguak Kabupaten Lima Puluh Kota - Fauzana Zafira; Yulhendri Yulhendri (Universitas Negeri Padang, 2022)
This study aims to see what factors influence women`s economic activities and what activities women do in improving the household economy, trade, and consumption, besides that it can also be seen from the social status of the woman which consists of the husband's income, education level, age, and the number of dependents. This research is a quantitative research approach with a survey method. The research variables consist of endogenous variables, namely economic participation(x) with indicators consisting of work, production, trade, and consumption as well as exogenous variables namely social status(Y) with the indicators being age, income, husband, education level, number of dependents in the family. Based on the results of this study, it shows that of the 4 factors the strongest is the level of education, the second is the husband's income factor, while the weak factor in influencing women's activities in improving the economy is the age factor and the number of dependents.